A state-dependent delay equation with chaotic solutions - Kennedy Benjamin B. (Electronic journal of qualitative theory of differential equations, 2019)
We exhibit a scalar-valued state-dependent delay differential equation x 0 (t) = f(x(t − d(xt))) that has a chaotic solution. This equation has continuous (semi-strictly) monotonic negative feedback, and the quantity t − d(xt) is strictly increasing along solutions.